2017
DOI: 10.1073/pnas.1706504114
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-related protein Vps34 controls the homeostasis and function of antigen cross-presenting CD8α+dendritic cells

Abstract: The class III PI3K Vacuolar protein sorting 34 (Vps34) plays a role in both canonical and noncanonical autophagy, key processes that control the presentation of antigens by dendritic cells (DCs) to naive T lymphocytes. We generated DC-specific Vps34-deficient mice to assess the contribution of Vps34 to DC functions. We found that DCs from these animals have a partially activated phenotype, spontaneously produce cytokines, and exhibit enhanced activity of the classic MHC class I and class II antigen-presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 51 publications
(51 reference statements)
3
49
0
Order By: Relevance
“…In line with this role of autophagy in presenting appropriate antigenic peptides, knockout of the autophagy‐regulator VPS34 in DCs abrogated the induction of B16 melanoma‐specific CTLs in vivo, yielding a significantly higher incidence of lung metastases . In this setting, cross‐presentation of OVA peptides derived from apoptotic cells was strongly reduced, although VPS34‐deficient DCs did present higher levels of cytoplasmic OVA‐derived antigens .…”
Section: Part Ii: the Role Of Autophagy In The Tumor Microenvironmentmentioning
confidence: 76%
“…In line with this role of autophagy in presenting appropriate antigenic peptides, knockout of the autophagy‐regulator VPS34 in DCs abrogated the induction of B16 melanoma‐specific CTLs in vivo, yielding a significantly higher incidence of lung metastases . In this setting, cross‐presentation of OVA peptides derived from apoptotic cells was strongly reduced, although VPS34‐deficient DCs did present higher levels of cytoplasmic OVA‐derived antigens .…”
Section: Part Ii: the Role Of Autophagy In The Tumor Microenvironmentmentioning
confidence: 76%
“…Mice with Atg5 deficient in DCs exhibited impaired activities of CD4 + T cells as a result of reduced interleukin (IL)-2 and interferon (IFN)-γ production, but without affecting costimulatory molecule expressions on DCs, which were different from Beclin-1 and vacuolar protein sorting 34 (Vps34). The DCs exhibited long-standing dysfunction and massive loss in animals with Beclin-1 or Vps34 deficient ( 34 36 ). However, Bhattacharya and colleagues found that the loss of Atg7 gene displayed protective effects against autoimmune encephalomyelitis in mice ( 37 ).…”
Section: Autophagy and Immune Responsementioning
confidence: 99%
“…17 Src, PI3K, and Akt are key genes affecting autophagy, and autophagy has been implicated in the antigen presentation ability and cytokine response of DCs. 34,35 Earlier reports showed that DAB2 was found to be an autophagy inhibitor by blocking the interaction between vacuolar protein sorting 34 and beclin-1. 36 To find out whether DAB2 affects the function of DCs through autophagy, we measured the autophagy proteins LC3 and P62 after overexpression of DAB2 in DCs but did not find a difference compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy can directly affect the maturation of DCs, 34,35 and DAB2 has been mentioned as an inhibitor of autophagy. 36 To investigate the role of DAB2 in the autophagy of DCs, we used Western blots to measure the autophagy proteins LC3 and P62 in DCs overexpressing DAB2.…”
Section: Autophagy Protein Lc3 and P62 Expression Were Not Affected Bmentioning
confidence: 99%